Contribution of longitudinal stiffener rigidity and position to bridge girder integrity (Fracture and Structural Integrity, 2019)
To increase the elastic critical load of a plate, such as I-shaped cross-welded section of bridge girders, slenderness is usually reduced by dividing the web into subpanels, by means of transversal stiffeners and a longitudinal stiffener to increase flexural and torsional stiffness. The optimal solution is defined when the stiffener maximizes the buckling coefficient, with a minimal cross-section area. For this purpose, seven forms of open and closed sections of longitudinal stiffeners, with differing second moment of area, are examined in terms of buckling coefficient by theoretical solution and numerical calculation, to compare their contribution in terms of weight per linear meter of beam. The optimum value of a conventional flat stiffener position, respect panel height and an useful practical law is given to correlate the best position with respect to variations in stress gradient, from pure bending to pure compression. This practical law facilities calculation regarding where to put a stiffener with respect to compressed edge in a web panel subjected to flexural-compressive loads, in order to maximize the benefit of its action and increase the stability of bridge girders.
Keywords: Bridge stability; Buckling coefficient; Optimal stiffness; Stiffener optimal positioning